Influence of Drying on the quality of Ashwagandha (Withania somnifera) - Agrawal, A (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
An experiment was carried out to adjudge the effect of different drying techniques on colour and withanolides content of Withania somnifera. Withania somnifera (Ashwagandha) is a plant used in medicine from the time of Ayurveda, the ancient system of Indian medicine and belong to the family Solanacae. The dried roots of the plant are used in the treatment of nervous and sexual disorders. From chemistry point of view, the drug contains group of biologically active constituents known as withanolides. Today there is much interest in natural products. The fresh Ashwagandha roots were dried in shade, sun and cabinet dryer. It was found that in cabinet drying about 49 to 52% moisture loss was observed in only 3.15 hours of drying. The drying condition does not affect much on colour but the effect of temperature plays an important role in withanolides content due to which maximum withanolides was observed in shade drying and minimum in case of cabinet drying (air velocity 1.8 - 2.0 ms-1).